Calculation of the Dynamic Responses of Rails Subjected to Moving Loads on Ballasted Railway Track - Le Hung, Tran; Dinh Duc, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 38 No 3DO - 10.25073/2588-1124/vnumap.4707, 2022)
The dynamical responses of railway track has been carried out by different ways. In this work, by developing an analytical model for the ballasted railway track which includes two rails connected to the railway sleeper, a fast method to calculated the dynamic responses of the two rails is presented. The rail is modelled as the infinite beams posed on the periodically supports which are rested on a viscoelastic foundation. We consider the dynamic equation in the steady-state of rails subjected to the moving loads. By using Fourier transform together the periodically conditions, a relation between the reaction force and the beam displacement in the frequency domain has been demonstrated. Then, by performing this relation into the dynamic equation of sleeper laying on viscoelastic foundation, the dynamic responses of the two rails can be obtained with a help of Green’s function. The numerical example demonstrates the effect of the support on the beam responses.